HIV diversity and drug resistance from plasma and non‐plasma analytes in a large treatment programme in western Kenya. Issue 2 (18th November 2014) - Kantor, Rami; DeLong, Allison; Balamane, Maya; Schreier, Leeann; Lloyd, Robert M; Injera, Wilfred; Kamle, Lydia; Mambo, Fidelis; Muyonga, Sarah; Katzenstein, David; Hogan, Joseph; Buziba, Nathan; et al.
Abstract : Introduction: Antiretroviral resistance leads to treatment failure and resistance transmission. Resistance data in western Kenya are limited. Collection of non‐plasma analytes may provide additional resistance information. Methods: We assessed HIV diversity using the REGA tool, transmitted resistance by the WHO mutation list and acquired resistance upon first‐line failure by the IAS–USA mutation list, at the Academic Model Providing Access to Healthcare (AMPATH), a major treatment programme in western Kenya. Plasma and four non‐plasma analytes, dried blood‐spots (DBS), dried plasma‐spots (DPS), ViveST TM ‐plasma (STP) and ViveST‐blood (STB), were compared to identify diversity and evaluate sequence concordance. Results: Among 122 patients, 62 were treatment‐naïve and 60 treatment‐experienced; 61% were female, median age 35 years, median CD4 182 cells/µL, median viral‐load 4.6 log10 copies/mL. One hundred and ninety‐six sequences were available for 107/122 (88%) patients, 58/62 (94%) treatment‐naïve and 49/60 (82%) treated; 100/122 (82%) plasma, 37/78 (47%) attempted DBS, 16/45 (36%) attempted DPS, 14/44 (32%) attempted STP from fresh plasma and 23/34 (68%) from frozen plasma, and 5/42 (12%) attempted STB. Plasma and DBS genotyping success increased at higher VL and shorter shipment‐to‐genotyping time. Main subtypes were A (62%), D (15%) and C (6%). Transmitted resistance was found in 1.8% of plasma sequences, and 7% combining analytes. Plasma resistance mutations were identified in 91% of treated patients, 76% NRTI, 91% NNRTI; 76% dual‐class; 60% with intermediate‐high predicted resistance to future treatment options; with novel mutation co‐occurrence patterns. Nearly 88% of plasma mutations were identified in DBS, 89% in DPS and 94% in STP. Of 23 discordant mutations, 92% in plasma and 60% in non‐plasma analytes were mixtures. Mean whole‐sequence discordance from frozen plasma reference was 1.1% for plasma‐DBS, 1.2% plasma‐DPS, 2.0% plasma‐STP and 2.3% plasma‐STB. Of 23 plasma‐STP discordances, one mutation was identified in plasma and 22 in STP ( p <0.05). Discordance was inversely significantly related to VL for DBS. Conclusions: In a large treatment programme in western Kenya, we report high HIV‐1 subtype diversity; low plasma transmitted resistance, increasing when multiple analytes were combined; and high‐acquired resistance with unique mutation patterns. Resistance surveillance may be augmented by using non‐plasma analytes for lower‐cost genotyping in resource‐limited settings.